Satellite observation of stratospheric intrusions and ozone transport using CrIS on SNPP. (15th March 2022) - Xiong, Xiaozhen; Liu, Xu; Wu, Wan; Knowland, K. Emma; Yang, Qiguang; Welsh, Jason; Zhou, Daniel K.
Abstract: The Single Field of View (SFOV) ozone (O3 ) profiles derived from the Cross-track Infrared Sounder (CrIS) onboard Suomi National Polar-Orbiting Partnership (SNPP), with a high horizontal resolution of approximately 14 km at nadir and good sensitivity to O3 in the upper troposphere and lower stratosphere (UTLS), provide a prominent opportunity to examine stratosphere to troposphere (STT) transport. A process-oriented analysis was performed to examine the fine-scale features of a stratospheric intrusion (SI) event on June 11–13, 2017 in the southwestern US using the CrIS SFOV products together with wind and potential velocity (PV) from models. It was found that the location and strength of O3 enhancement correlate well with the PV contours, and the intrusion depth can be characterized using the vertical cross-sections of O3 and relative humidity (RH). In addition, the capability to use total column ozone (TCO) to identify SI events was confirmed through analysis of TCO from CrIS SFOV and other satellite and reanalysis products. The ozone/PV ratio was derived using SFOV O3 and model PV, and the values, ranging from 23.2 to 35.8 ppbv PVU −1 (1 PV unit (PVU) = 10 −6  km 2  kg −1 s −1 ), are in the lower end of previous estimations. These results demonstrate the advantages of the SFOV products in monitoring the fine-scale ozone transport and thermodynamic structure of SI events, as well as their potential value for weather and climate study. Highlights: CrIS SFOV products with a high horizontal resolution of 14 km can capture the fine-scale features of a SI and associated O3 transport. The location of O3 enhancement correlates well with PV contours, and the O3 intrusion depth matches well with the tropopause. Enhancement of CrIS total O3 associated with a SI agree with OMPS and AIRS products and the MERRA-2 and ERA-5 reanalysis. Th O3 /PV ratio derived using SFOV O3 and reanalysis PV ranges from 23.2 to 35.8 ppbv/PVU and is on the lower end of previous studies.